c) 82019.(x-2)3=82020
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 2:
\(x^3+4x^2-7x-10\)
\(=x^3+5x^2-x^2-5x-2x-10\)
\(=\left(x+5\right)\left(x^2-x-2\right)\)
\(=\left(x+5\right)\left(x-2\right)\left(x+1\right)\)
\(\begin{array}{l}A + B + C\\ = (3{x^4} - 2{x^3} - x + 1) + ( - 2{x^3} + 4{x^2} + 5x) + ( - 3{x^4} + 2{x^2} + 5)\\ = 3{x^4} - 2{x^3} - x + 1 - 2{x^3} + 4{x^2} + 5x - 3{x^4} + 2{x^2} + 5\\ = (3{x^4} - 3{x^4}) + ( - 2{x^3} - 2{x^3}) + (4{x^2} + 2{x^2}) + ( - x + 5x) + (1 + 5)\\ = 0 + ( - 4{x^3}) + 6{x^2} + 4x + 6\\ = - 4{x^3} + 6{x^2} + 4x + 6\\A - B + C\\ = (3{x^4} - 2{x^3} - x + 1) - ( - 2{x^3} + 4{x^2} + 5x) + ( - 3{x^4} + 2{x^2} + 5)\\ = 3{x^4} - 2{x^3} - x + 1 + 2{x^3} - 4{x^2} - 5x - 3{x^4} + 2{x^2} + 5\\ = (3{x^4} - 3{x^4}) + ( - 2{x^3} + 2{x^3}) + ( - 4{x^2} + 2{x^2}) + ( - x - 5x) + (1 + 5)\\ = 0 + 0 + ( - 2{x^2}) - 6x + 6\\ = - 2{x^2} - 6x + 6\\A - B - C\\ = (3{x^4} - 2{x^3} - x + 1) - ( - 2{x^3} + 4{x^2} + 5x) - ( - 3{x^4} + 2{x^2} + 5)\\ = 3{x^4} - 2{x^3} - x + 1 + 2{x^3} - 4{x^2} - 5x + 3{x^4} - 2{x^2} - 5\\ = (3{x^4} + 3{x^4}) + ( - 2{x^3} + 2{x^3}) + ( - 4{x^2} - 2{x^2}) + ( - x - 5x) + (1 - 5)\\ = 6{x^4} + 0 + ( - 6{x^2}) - 6x + ( - 4)\\ = 6{x^4} - 6{x^2} - 6x - 4\end{array}\)
a: Trường hợp 1: x<-1
A=3(-x-1)+2(-x+3)+2x-5
=-3x-3-2x+6+2x-5
=-3x-2
Trường hợp 2: -1<=x<3
A=3(x+1)+2(3-x)+2x-5
=3x+3+6-2x+2x-5
=3x+4
Trường hợp 3: x>=3
A=3(x+1)+2(x-3)+2x-5
=3x+3+2x-6+2x-5
=7x-8
b: Trường hợp 1: x<-7
B=-x-7+2(3-x)-x-4
=-2x-11+6-2x=-4x-5
TRường hợp 2: -7<=x<3
B=x+7+2(3-x)-x-4
=3+6-2x=-2x+9
Trường hợp 3: x>=3
B=x+7+2x-6-x-4=2x-3
c: Trường hợp 1: x<1
C=8(1-x)+2(3-x)-5x-3
=8-8x+6-2x-5x-3
=-15x+11
Trường hợp 2: 1<=x<3
C=8(x-1)+2(3-x)-5x-3
=8x-8+6-2x-5x-3
=x-5
TRường hợp 3: x>=3
C=8(x-1)+2(x-3)-5x-3
=8x-8+2x-6-5x-3
=5x-17
a: Trường hợp 1: x<-1
A=2(3-x)+3(-x-1)+2x-5
=6-2x-3x-3+2x-5
=-3x-2
Trường hợp 2: -1<=x<3
A=2(3-x)+3(x+1)+2x-5
=6-2x+3x+3+2x-5
=3x+4
TRường hợp 3: x>=3
A=2(x-3)+3(x+1)+2x-5
=2x-6+3x+3+2x-5
=7x-8
b: Trường hợp 1: x<-7
B=7-x+2(3-x)-x-4
=3-2x+6-2x=-4x+9
Trường hợp 2: -7<=x<3
B=x+7+2(3-x)-x-4
=3+6-2x=-2x+9
Trường hợp 3: x>=3
B=x+7+2x-6-x-4=2x-3
`@` `\text {Ans}`
`\downarrow`
`B(x)-A(x)+C(x)`
`=`\((x^2-5x^3-4x+7) - (-x^3 + 7x^2 +2x - 15) + 3x^3 - 7x^2 -4\)
`=`\(x^2-5x^3-4x+7+x^3-7x^2-2x+15+3x^3-7x^2-4\)
`=`\(\left(-5x^3+x^3+3x^3\right)+\left(x^2-7x^2-7x^2\right)+\left(-4x-2x\right)+\left(7+15-4\right)\)
`=`\(-x^3-13x^2-6x+18\)
`C(x)-B(x)-A(x)`
`=`\(3x^3 - 7x^2 -4 - (x^2-5x^3-4x+7) - (-x^3 + 7x^2 +2x - 15)\)
`=`\(3x^3-7x^2-4-x^2+5x^3+4x-7+x^3-7x^2-2x+15\)
`=`\(\left(3x^3+5x^3+x^3\right)+\left(-7x^2-x^2-7x^2\right)+\left(4x-2x\right)+\left(-4-7+15\right)\)
`=`\(9x^3-15x^2+2x+4\)
a) \(B\left(x\right)-A\left(x\right)+C\left(x\right)\)
\(=\left(x^2-5x^3-4x+7\right)-\left(-x^3+7x^2+2x-15\right)+\left(3x^3-7x^2-4\right)\)
\(=x^2-5x^3-4x+7+x^3-7x^2-2x+15+3x^3-7x^2-4\)
\(=\left(-5x^3+x^3+3x^3\right)+\left(x^2-7x^2-7x^2\right)-\left(4x+2x\right)+\left(7-4+15\right)\)
\(=-x^3-13x^2-6x+18\)
b) \(C\left(x\right)-B\left(x\right)-A\left(x\right)\)
\(=\left(3x^3-7x^2-4\right)-\left(x^2-5x^3-4x+7\right)-\left(-x^3+7x^2+2x-15\right)\)
\(=3x^3-7x^2-4-x^2+5x^3+4x-7+x^3-7x^2-2x+15\)
\(=\left(3x^3+5x^3+x^3\right)-\left(7x^2+x^2+7x^2\right)+\left(4x-2x\right)-\left(4+7-15\right)\)
\(=9x^3-15x^2+2x+4\)
Bài 1:
Ta có: \(a^3+b^3+c^3=3abc\)
\(\Leftrightarrow\left(a^3+3a^2b+3ab^2+b^3\right)+c^3-3a^2b-3ab^2-3abc=0\)
\(\Leftrightarrow\left(a+b\right)^3+c^3-3ab\left(a+b+c\right)=0\)
\(\Leftrightarrow\left(a+b+c\right)\left[\left(a+b\right)^2-\left(a+b\right)c+c^2\right]-3ab\left(a+b+c\right)=0\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ac\right)=0\)
\(\Leftrightarrow a^2+b^2+c^2-ab-bc-ac=0\left(do.a+b+c\ne0\right)\)
\(\Leftrightarrow2\left(a^2+b^2+c^2-ab-bc-ac\right)=0\)
\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(a-c\right)^2=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(a-b\right)^2=0\\\left(b-c\right)^2=0\\\left(a-c\right)^2=0\end{matrix}\right.\)\(\Leftrightarrow a=b=c\)
\(M=\dfrac{a^2+b^2+c^2}{\left(a+b+c\right)^2}=\dfrac{3a^2}{\left(3a\right)^2}=\dfrac{3a^2}{9a^2}=\dfrac{1}{3}\)
Bài 2:
a) \(=\dfrac{x\left(x^2+x-6\right)}{x\left(x^2-4\right)}=\dfrac{x\left(x-2\right)\left(x+3\right)}{x\left(x-2\right)\left(x+2\right)}=\dfrac{x+3}{x+2}\)
b) \(=\dfrac{x\left(x+1\right)+7\left(x+1\right)}{x\left(x^2+2x+1\right)}=\dfrac{\left(x+1\right)\left(x+7\right)}{x\left(x+1\right)^2}=\dfrac{x+7}{x\left(x+1\right)}=\dfrac{x+7}{x^2+x}\)